Heat stress decreases the diversity, abundance and functional potential of coral gas emissions. (30th November 2020) - Lawson, Caitlin A.; Raina, Jean‐Baptiste; Deschaseaux, Elisabeth; Hrebien, Victoria; Possell, Malcolm; Seymour, Justin R.; Suggett, David J.
Abstract: Terrestrial ecosystems emit large quantities of biogenic volatile organic compounds (BVOCs), many of which play important roles in abiotic stress responses, pathogen and grazing defences, inter‐ and intra‐species communications, and climate regulation. Conversely, comparatively little is known about the diversity and functional potential of BVOCs produced in the marine environment, especially in highly productive coral reefs. Here we describe the first 'volatilomes' of two common reef‐building corals, Acropora intermedia and Pocillopora damicornis, and how the functional potential of their gaseous emissions is altered by heat stress events that are driving rapid deterioration of coral reef ecosystems worldwide. A total of 87 BVOCs were detected from the two species and the chemical richness of both coral volatilomes—particularly the chemical classes of alkanes and carboxylic acids—decreased during heat stress by 41% and 62% in A. intermedia and P. damicornis, respectively. Across both coral species, the abundance of individual compounds changed significantly during heat stress, with the majority (>86%) significantly decreasing compared to control conditions. Additionally, almost 60% of the coral volatilome (or 52 BVOCs) could be assigned to four key functional groups based on their activities in other species or systems, including stress response, chemical signalling, climate regulation and antimicrobial activity. The total number of compounds assigned to these functions decreased significantly under heat stress for both A. intermedia (by 35%) and P. damicornis (by 64%), with most dramatic losses found for climatically active BVOCs in P. damicornis and antimicrobial BVOCs in A. intermedia . Together, our observations suggest that future heat stress events predicted for coral reefs will reduce the diversity, quantity and functional potential of BVOCs emitted by reef‐building corals, potentially further compromising the healthy functioning of these ecosystems. Abstract : Biogenic volatile organic compounds (BVOCs) are vital gases capable of regulating the healthy functioning of terrestrial ecosystems as they undergo global change, but their diversity and function in marine ecosystems, and notably in highly biodiverse coral reefs, is unknown. This is the first study bridging this gap; two species of key reef‐building corals were shown to emit numerous BVOCs that also changed during heat stress. Assigning putative functions to these BVOCs revealed a hidden world of functionally active gases and potential chemical communication. By exploring these coral gases, we gain new understanding of the hidden drivers of coral reef survival.